Pemberdayaan Kader Posyandu dalam Peningkatan Kesehatan Lansia Hipertensi - Cipto Cipto; Siswoko Siswoko; Ajeng Titah Normawati (LPPM Universitas Harapan Bangsa Purwokerto, 2026)
Hypertension is a major health problem in the elderly, putting them at risk of stroke, heart disease, and other cardiovascular complications. The role of Posyandu Lansia cadres is crucial in supporting promotive and preventive efforts, but their skills in health education, blood pressure monitoring, and mentoring the elderly still need to be improved. This community service activity aims to improve the knowledge and skills of cadres in managing hypertension in the elderly at the Posyandu Lansia in Gempolrejo Village, Tunjungan District, Blora Regency. The methods used included counseling, training in blood pressure measurement using a digital sphygmomanometer, health communication training, education on preventing hypertension complications, and evaluation through pre- and post-tests. The activity was attended by 15 health cadres. The results showed an increase in cadre knowledge, marked by an increase in the average score from 62.3±8.7 in the pre-test to 87.7±6.5 in the post-test, an increase of 25.4 points or 40.8%. In addition, the proportion of cadres with good knowledge increased from 20.0% to 86.7%. This activity effectively increased the capacity of cadres in health education, blood pressure monitoring, and mentoring elderly people with hypertension. Empowering Posyandu (Lansia Integrated Health Post) cadres can be a sustainable strategy for improving the health of elderly people with hypertension in the community. Keywords: health cadres, hypertension, elderly, Posyandu